2012
DOI: 10.5574/ijose.2011.2.2.082
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Welding Residual Stress Distribution on T-joint Fillet Structure

Abstract: Fillet welding is widely used in the assembly of ships and offshore structures. The T-joint configuration is frequently reported to experience fatigue damage when a marine structure meets extreme loads such as storm loads. Fatigue damage is affected by the magnitude of residual stresses on the weld. Recently, many shipping registers and design guides have required that the fatigue strength assessment procedure of seagoing structures under waveinduced random loading and storm loading be compensated based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Results showed that except the starting location, there is no effective difference in the axial and hoop residual stresses in the welded pipe. 14 Computational procedure is proposed by the Hwang et al 15 in which the residual stresses in the welded T-joint are measured using the X-ray diffraction (XRD). The 3D FE analysis was done to find out the profile of the residual stresses, and the proposed model was validated with the experimental result.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that except the starting location, there is no effective difference in the axial and hoop residual stresses in the welded pipe. 14 Computational procedure is proposed by the Hwang et al 15 in which the residual stresses in the welded T-joint are measured using the X-ray diffraction (XRD). The 3D FE analysis was done to find out the profile of the residual stresses, and the proposed model was validated with the experimental result.…”
Section: Introductionmentioning
confidence: 99%